Trustworthiness requirement‐oriented software process modeling. Issue 12 (15th October 2018) - Zhang, Xuan; Wang, Xu; Kang, YanNi
Abstract: Trustworthy software is delivered by enacting trustworthy software processes. The purpose of this paper is to propose an approach to modeling trustworthiness requirement‐oriented software processes. First, based on the aspect‐oriented modeling techniques, separation of concerns is used to separate the crosscutting activities and the core activities according to the different trustworthiness requirements and functional requirements. A goal‐oriented modeling and reasoning method for trustworthiness requirements to find the crosscutting activities that satisfy multiple trustworthiness requirements is presented. Then, base processes are modeled for functional requirements. The crosscutting activities for trustworthiness requirements are decomposed into processes or tasks and encapsulated in aspects that are woven into the base processes. In the weaving procedure, correct weaving methods between multiple aspects and between aspects and base processes are designed. Errors or mistakes of aspect‐oriented process modeling are prevented. Finally, trustworthy third‐party certification authority software is studied systematically in a case study, and performance evaluations are conducted to show the cost and effect of the approach. Abstract : This paper proposes an approach to modeling trustworthiness requirement‐oriented software processes. These processes deliver trustworthiness by introducing trustworthiness goal‐oriented activities (TG_activities) and ensuring the correctness of the process modeling. When integrating TG_activities into software processes, aspect‐oriented modeling techniques are adopted. Correctness of the integration between multiple TG_activities and between TG_activities and software processes are analyzed, and correct integration methods are designed. The proposed approach of process modeling can adequately match the evolutions and changes in the trustworthiness requirements.